Pengaruh Task Analysis untuk Meningkatkan Kemampuan Merawat Diri saat Menstruasi pada Siswa Tunagrahita di SLB C YKB Garut - Tuti Nuruli Adha (Jurnal Penelitian Pendidikan Khusus, 2022)
The purpose of this study is to determine the effect of task analysis to improve self-care ability during menstruation for mentally retarded student at SLB C YKB Garut. The research method used is a quantitative method with a single subject experimental research (SSR). This single subject study used an A-B-A reversal design, namely the baseline-1 (A1) phase of 5 sessions, the intervention phase (B) of 10 sessions, and the baseline-2 phase (A2) of 5 sessions. The subject of the study was a sixth grade mentally retarded student at SLB C YKB Garut who had not been able to take care of herself during menstruation. The data collection technique used is a performance test and then for data analysis techniques using descriptive statistical techniques with visual analysis. The results of the study indicate that task analysis has an effect on increasing the ability to take care of herself during menstruation in mentally retarded students at SLB C YKB Garut. The increase in the subject's ability is indicated by a change in the mean level in each phase, namely the baseline-1 phase (A1) by 32.942% then in the intervention phase (B) to 85.73%, and the mean level in the baseline-2 phase (A2) by 73 ,47%. The conclusion of this study is that task analysis has an effect on improving the ability to take care of oneself during menstruation for mentally retarded students at SLB C YKB Garut.